Peran Religiusitas dalam Memoderasi Disposable Income dan Pengetahuan Perbankan Syariah terhadap Minat Menabung di Bank Syariah - Sugesti, Putri; Hakim, Luqman (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to analyze the effect of income and knowledge of Islamic banking on interest in saving in Islamic banks with religiosity as a moderating variable. This type of research is quantitative research using data techniques through questionnaires. The population of this study were students at 3 State Universities in Surabaya, namely Sunan Ampel State Islamic University Surabaya, Surabaya State University, and Airlangga University. The sample of this research is 100 students of the Sharia economics study program at 3 State Universities in Surabaya. Technical analysis of the data used the multivariant statistical method of Structural Equation Modeling (SEM) using Partile Least Square (PLS) and calculated using the Warp PLS 6.0 computer program. The sampling technique used purposive sampling, namely by using special criteria that have been determined by the researcher. The results of this study are that there is a positive effect of disposable income on interest in saving, knowledge of Islamic banking has an effect on interest in saving, religiosity cannot moderate disposable income on interest in saving, and knowledge of Islamic banking is moderated by religiosity on interest in saving.